Why Should We Think Critically? Comments on the Critical Rationalism of Hans Albert - Wieczorek, Krzysztof T. (Folia Philosophica, 2018)
Leszek Kołakowski draws attention to the fact that rationalism as a philosophical method and definitive certainty as the aim are mutually irreconcilable. Each rationalist philosophy must leave a margin for uncertainty, lest it transforms into dull dogmatism. This observation of the Polish thinker becomes a source of inspiration for Hans Albert. In his work “Science and the Search for Truth”, he agrees with Kołakowski that goals of philosophical endeavours need redefining and puts forward his own metaphilosophical proposal, which specifies what philosophy can and should achieve in the framework of critical realism. The author examines and evaluates Albert’s proposal, referring to another view of the nature and role of philosophy as the assessment criterion—the one presented by José Ortega y Gasset in his study “En torno à Galileo” [“About Galileo”] and other writings.